FORMATION OF STRATEGIC RESILIENCE OF ENTERPRISES BASED ON PERSONNEL DEVELOPMENT (INNOVATIVE ECONOMY, 2025)
Brych V.Ya.  FORMATION OF STRATEGIC RESILIENCE OF ENTERPRISES BASED ON PERSONNEL DEVELOPMENTPurpose. The aim is to investigate how personnel development shapes the strategic sustainability of enterprises in conditions of turbulence and uncertainty.Methodology of research. Methods of analysis and synthesis of scientific sources, systematization of HR statistics, analytical comparison of indicators of personnel retention, turnover and engagement were used. A structural and logical analysis of factors of stability and HR practices was conducted.Findings. It is shown that investments in professional development are directly correlated with personnel retention: 93% of employees are ready to stay in the company longer if there is career growth, and the priority of well-being reduces turnover by 40%. The growth trends in training costs (from $ 1,280 to $ 1,490 per employee in 2022–2024) and the structure of popular training methods are systematized. It is shown that the largest gaps are in digital literacy, communication and leadership, data analysis and change management. Four key elements of resilience through HR development are summarized: continuous learning and competence development; knowledge management and innovation; motivation, involvement and support for well-being; adaptability of organizational structures and flexibility of employees. It has been established that the synergy of these elements ensures the ability of an enterprise to quickly adapt processes, maintain important competencies, and increase productivity during crisis changes.Originality. The substantiation of the role of personnel development in shaping the strategic sustainability of enterprises has been further developed. Unlike common approaches, where resilience is considered through the prism of technological, resource or financial determinants, the work substantiates the need to take into account the human dimension as a key carrier of adaptability and recovery capabilities of the organization. The content of the components of personnel development (competences, knowledge, motivation, adaptability) is specified, through which the individual flexibility of employees is transformed into the macro-level sustainability of the enterprise. Practical value. The practical value of the work lies in the formation of managerial conclusions on how enterprises can increase strategic resilience through systemic HR practices. The obtained results may be useful for HR managers, business leaders, consultants in organizational development and anti-crisis management.Key words: organizational resilience, human capital, knowledge and innovation, personal, motivation, future skills, sustainability, resilience, flexibility, adaptation, uncertainty.
Keywords: organizational resilience; human capital; knowledge and innovation; personal; motivation; future skills; sustainability; resilience; flexibility; adaptation; uncertainty